2021
DOI: 10.21203/rs.3.rs-142059/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Long-term Nonylphenol Exposure on Myocardial Fibrosis and Cardiac Function in Rats

Abstract: Background: Myocardial fibrosis is a critical pathological basis for the poor prognosis of cardiovascular diseases. Studies have found that myocardial fibrosis is closely associated with exposure to environmental estrogens such as nonylphenol (NP), as a representative of environmental estrogens. The aim of this study was to examine the effects of NP chronic exposure on myocardial fibrosis as well as cardiac structure and function. Forty Sprague Dawley rats were randomly divided into four groups (n = 10): contr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
(37 reference statements)
1
5
1
Order By: Relevance
“…At systemic level, D-gal is also described to decrease antioxidant and total antioxidant capacity levels [413]. However, in this study, D-gal only induced moderate changes at cardiac and systemic level: for example, no differences were observed between healthy and D-gal animals at hemodynamic and cardiac perfusion level and only moderate changes in GLB1 expression, hypertrophy and cardiac fibrosis were observed, being the values and differences still far from those of naturally aged of pathological animals [140,[414][415][416]. Therefore, as D-gal did not induce large damage at cellular, structural, and functional level, we cannot consider these animals as truly aged or pathological, giving little room for the P-EVs to exert any significant benefits.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…At systemic level, D-gal is also described to decrease antioxidant and total antioxidant capacity levels [413]. However, in this study, D-gal only induced moderate changes at cardiac and systemic level: for example, no differences were observed between healthy and D-gal animals at hemodynamic and cardiac perfusion level and only moderate changes in GLB1 expression, hypertrophy and cardiac fibrosis were observed, being the values and differences still far from those of naturally aged of pathological animals [140,[414][415][416]. Therefore, as D-gal did not induce large damage at cellular, structural, and functional level, we cannot consider these animals as truly aged or pathological, giving little room for the P-EVs to exert any significant benefits.…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, although the results go in the direction of our hypothesis and show differences between the changes induced by EVs classified as potent and non-potent in vivo, the cardiac aging model used also presents some limitations. In particular, we only observed moderate differences between healthy and D-gal (aged) animals at molecular and structural level, and none at functional level, being the values and differences still far from those of naturally aged of pathological animals [140,[414][415][416]. This, together with the relatively low number of animals included in this study, make it difficult to see the potential small differences caused either by the model or by the potent EVs.…”
Section: Limitationsmentioning
confidence: 64%
“…NP is mainly metabolized in the liver and kidney and accumulated in lipolytic organs. Our study showed that cardiac tissue accumulation reached 54.61 ng/mg after 180 days of exposure to 40 mg/kg NP 1 . It has also been reported that up to 80% of orally ingested NP is rapidly absorbed 2 and metabolized by the liver with high hepatic and renal clearance 3 .…”
Section: Introductionsupporting
confidence: 65%
“…NP is toxic to multiple organs and systems 33 . Our prior studies demonstrated that heart is the target organ of NP's toxicity 1 . In this study, the long‐term intragastric administration of NP to rats and the intervention of ordinary green tea and zinc‐selenium tea were the first to explore the effect of tea on the cardiotoxicity of rats caused by NP exposure, and then to compare the intervention of zinc‐selenium tea and ordinary green tea.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation